Práticas discursivas e construção da participação e da fala em uma turma de alfabetização - Marco Antonio Melo Franco (2002)
Considering that during the process of learning how to write and read, writing skills are favored over speaking skills - being so, many times the speaking skills are used only as a support tool to the writing skills. This research aims to describe and analyze how the students speaking skills and their interaction in this process are being tapped in the classroom. In this case, the theoretical reflections of this study concerning the learning process of how to read and write present discussions on teaching-learning processes of writing and reading and particularly, on the role given to speaking and interaction in this context. Aspects related to the interaction and speech practices in the classroom were taken into consideration, as fundamental for understanding how participants express themselves, become involved and bring into the classroom their day to day experiences. (Moita Lopes, 1998). Therefore, this analysis has followed the interpretation approach. This choice of methodology can be explained by the fact that we work with interaction in the classroom which, through this paradigm, allows to interpret the relationship established between the teacher and the students from speech practices developed in that context which allows for the construction of students speaking and interaction skills. In this way, we have analyzed the speech interactions in the process of learning how to read and write in the classroom environment, observing to what degree the teachers participation facilitates the construction of such space. At first the analysis showed that, since the first day of class the teacher had tried to encourage students speaking and interaction skills by raising questions and problems, giving importance to speaking and valuing their experiences. In a second moment, it was possible to conclude that her actions indicated the limits and rules for building interaction and speaking in the classroom. She tried to build and to ensure the interaction space making students take sides in the face of different situations that would occur in the classroom. In a third moment, through the observation of reading activities, we noticed that the dynamics established during these activities, concerning interaction and speaking, does not differ from many other moments during classes. They occur during debates, discussions, speaking situations and argumentations that aim to build the interaction space. Finally, the last analysis phase has revealed that the teacher, although facing some difficulties in conducting this democratic and participating process, insisted on her objective. Through a joint-elaboration project, she tried to make the students co-participants in the re-elaboration of the concept of interaction. This study has thus shown that the teachers actions point to a concern on building a space appropriate to the process of learning how to read and write where students can participate, speak and express themselves, in the face of different situations that may occur during classes. The teacher uses this set of elements as constitutive of the reading and writing learning process. Through her actions and speech practices she has tried to lead the students to build the concept of interaction and to understand the interaction possibilities in the classroom.